2019
DOI: 10.7150/jca.27491
|View full text |Cite
|
Sign up to set email alerts
|

A network-based approach to identify DNA methylation and its involved molecular pathways in testicular germ cell tumors

Abstract: Background : Testicular germ cell tumors (TGCT) is the most common testicular malignancy threaten young male reproductive health. This study aimed to identify aberrantly methylated-differentially expressed genes and pathways in TGCT by comprehensive bioinformatics analysis. Methods : Data of gene expression microarrays (GSE3218, GSE18155) and gene methylation microarrays (GSE72444) were collected from GEO database. Integrated analysis acquired aberrantly methylated-genes. Fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 68 publications
1
12
0
Order By: Relevance
“…Furthermore, locus specific promoter methylation occurs in nonseminoma that is distinct for each histological type, again with a general pattern of increased methylation with increased differentiation status [ 25 , 101 , 102 ]. This includes evidence that methylation of such genes as CRIPTO , HOXA9 MGMT , RASSFIA , SCGB3A1 , CALCA , MMP9 , CSFR1 , and PTPRC is associated with distinct TGCT subtypes or poor prognosis [ 101 , 114 , 115 , 116 , 118 ].…”
Section: Epigenetic States In Testicular Germ Cell Tumors Associatmentioning
confidence: 99%
“…Furthermore, locus specific promoter methylation occurs in nonseminoma that is distinct for each histological type, again with a general pattern of increased methylation with increased differentiation status [ 25 , 101 , 102 ]. This includes evidence that methylation of such genes as CRIPTO , HOXA9 MGMT , RASSFIA , SCGB3A1 , CALCA , MMP9 , CSFR1 , and PTPRC is associated with distinct TGCT subtypes or poor prognosis [ 101 , 114 , 115 , 116 , 118 ].…”
Section: Epigenetic States In Testicular Germ Cell Tumors Associatmentioning
confidence: 99%
“…At present, few bioinformatics analyses have been conducted to investigate DEGs and DEMs in seminoma. Of the DEGs screened in this study, only TOP2A and PTPRC have been reported in seminoma (59,60), to the best of our knowledge. Additionally, we screened the differential expression of genes from array data and predicted target genes of DEMs which were proposed to act together on the PI3K/AKT and Wnt/β-catenin signalling pathways with a strong correlation (29,39).…”
Section: Discussionmentioning
confidence: 89%
“…TGCT occurs in young men, posing a huge threat to the life and reproductive health of young male patients, but the pathogenesis has not been fully elucidated. Many studies have shown that genetic factors and epigenetic factors are closely related to the occurrence and development of TGCT 25 27 . METTL3 is an important molecule that regulates m6A modification in epigenetics and can initiate meiosis by promoting the differentiation process of spermatogenesis 28 .…”
Section: Discussionmentioning
confidence: 99%